Legal Review of Default (Wanprestatie) in Gas Cylinder Lease Agreement - Jesika Rekma Lela; Risti Dwi Ramasari (Universitas PGRI Madiun, 2022)
This research is to obtain legal protection for the people in Bandar Lampung City, the Act is enacted as a guide in the law that regulates legal relations between humans with one another. Which gives rise to rights and obligations between the two which are commonly known as agreements. There are various kinds of agreements, such as a lease purchase, in which the prospective buyer becomes a tenant first before paying off the goods he wants to buy. This relationship creates a legal relationship where in a relationship there is a denial of obligation or default. Which can cause problems between both parties. The problems that occur are resolved either by peaceful means or through the courts. In this study using a normative juridical approach, as well as an empirical approach. The problem that will be raised in this research is how the legal consequences and how the judge's consideration in making a decision